The prevalence of hypertension during Ramadan - Othman, Noratikah; Mohamad Soki, Nur Akma; Jamaludin, Thandar Soe Sumaiyah (Medwin Publishers, 2019)
Objective: This study was aimed to identify the prevalence of hypertension during the month of Ramadan in Kuantan as well as to compare the mean differences of blood pressure with pre, during and post Ramadan. Methods: A retrospective cohort study by using purposive sampling with sample size of 66 hypertensive patients at Medical Outpatient Department (MOPD), Hospital Tengku Ampuan Afzan (HTAA), Kuantan was conducted. The data collection form was used as a research instrument to obtain data from hospital record. The data was analysed by using SPSS version 22 in term of descriptive analysis (frequency and percentage), and T-test for the significant differences. Results: The majority of participant’s age from 61 to 70 years old (34.8%). For BMI, about 43 participants (65.2%) were overweight or obese and the remaining 34.8% were in normal BMI. Besides, about 30.0% were smokers. The prevalence of hypertension can be divided into two which are systolic blood pressure and diastolic blood pressure. About 66.7% participants were affected at systolic area. In addition, about 16.7% participants were affected at diastolic area. For independent T-test, there was no significant differences of systolic blood pressure and fasting with p-value 0.53. Besides, there was no significant differences of diastolic blood pressure and fasting with p-value 0.60. Furthermore, for paired Ttest, there were significant differences in mean of blood pressure between pre, during and post Ramadan with p-value 0.00. Conclusion: Prevalence of hypertension during Ramadan can be indicator to prevent hypertension as well as to promote awareness to other people. Hence, the health care provider can educate people about modified diet or fasting can help in reducing the case of cardiovascular disease.